Cosmological gravitational waves from isocurvature fluctuations - Guillem Domènech (AAPPS Bulletin, 2024)
Abstract Gravitational waves induced by large primordial curvature fluctuations may result in a sizable stochastic gravitational wave background. Interestingly, curvature fluctuations are gradually generated by initial isocurvature fluctuations, which in turn induce gravitational waves. Initial isocurvature fluctuations commonly appear in multi-field models of inflation as well as in the formation of scattered compact objects in the very early universe, such as primordial black holes and solitons like oscillons and cosmic strings. Here, we provide a review on isocurvature induced gravitational waves and its applications to dark matter and the primordial black hole dominated early universe.